Validación concurrente del proceso de manufactura de tabletas de loratadina 10 mg / dexametasona 2 mg, en un laboratorio nacional. Lima – 2017. - Díaz Baltodano, Carlos Andrés (2019)
The purpose of this report on Pre - Professional Practices is to determine whether the concurrent validation of the loratadine 10 mg / dexamethasone 2 mg tablet manufacturing process manufactured by a national laboratory complies with the parameters of concurrent validation established by Good Manufacturing Practices (GMP). The quality of the physical parameters of the final mixture was determined; appearance, density and humidity. Subsequently, the quality of the physicochemical parameters was determined during the compression process; appearance, weight variation, average weight, dimensions, hardness, disintegration, friability, dissolution and valuation. With the results obtained from the average weight and assessment parameters, a statistical control analysis was performed with X-R control graphs and capacity studies (Cp and Cpk). It was finally concluded that the manufacturing process of loratadine tablets 10 mg / dexamethasone 2 mg meets the parameters of concurrent validation and fully satisfies the specifications